Protective effect of rhodioloside and bone marrow mesenchymal stem cells infected with HIF-1-expressing adenovirus on acute spinal cord injury - Ha, Xiao-Qin (Neural Regen Res, 2019)
Rhodioloside has been shown to protect cells from hypoxia injury, and bone marrow mesenchymal stem cells have a good effect on tissue repair. To study the effects of rhodioloside and bone marrow mesenchymal stem cells on spinal cord injury, a rat model of spinal cord injury was established using the Infinite Horizons method. After establishing the model, the rats were randomly divided into five groups. Rats in the control group were intragastrically injected with phosphate buffered saline (PBS) (5 μL). PBS was injected at 6 equidistant points around 5 mm from the injury site and at a depth of 5 mm. Rats in the rhodioloside group were intragastrically injected with rhodioloside (5 g/kg) and intramuscularly injected with PBS. Rats in the mesenchymal stem cell (MSC) group were intramuscularly injected with PBS and intramuscularly with MSCs (8 × 10(6)/mL in a 50-μL cell suspension). Rats in the Ad-HIF-MSC group were intragastrically injected with PBS and intramuscularly injected with HIF-1 adenovirus-infected MSCs. Rats in the rhodioloside + Ad-HIF-MSC group were intramuscularly injected with MSCs infected with the HIF-1 adenovirus and intragastrically injected with rhodioloside. One week after treatment, exercise recovery was evaluated with a modified combined behavioral score scale. Hematoxylin-eosin staining and Pischingert’s methylene blue staining were used to detect any histological or pathological changes in spinal cord tissue. Levels of adenovirus IX and Sry mRNA were detected by real-time quantitative polymerase chain reaction and used to determine the number of adenovirus and mesenchymal stem cells that were transfected into the spinal cord. Immunohistochemical staining was applied to detect HIF-1 protein levels in the spinal cord. The results showed that: (1) compared with the other groups, the rhodioloside + Ad-HIF-MSC group exhibited the highest combined behavioral score (P < 0.05), the most recovered tissue, and the greatest number of neurons, as indicated by Pischingert’s methylene blue staining. (2) Compared with the PBS group, HIF-1 protein expression was greater in the rhodioloside group (P < 0.05). (3) Compared with the Ad-HIF-MSC group, Sry mRNA levels were higher in the rhodioloside + Ad-HIF-MSC group (P < 0.05). These results confirm that rhodioloside combined with bone marrow mesenchymal stem cells can promote the recovery of spinal cord injury and activate the HIF-1 pathway to promote the survival of bone marrow mesenchymal stem cells and repair damaged neurons within spinal cord tissue. This experiment was approved by the Animal Ethics Committee of Gansu University of Traditional Chinese Medicine, China (approval No. 2015KYLL029) in June 2015.